An Empirical Investigation of Maintainability Metrics Adoption in Brazilian Software Companies - Soares, Micael; Romeiro, Samuel; Saraiva, Juliana; Soares, Sérgio (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2016: Anais do XV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2016.15124, 2016)
Software Maintainability (SM) has been studied since it became globally accepted as part of the software quality model. Many researchers have been proposing a lot of metrics to be used as SM indicators. Nevertheless, the descriptions of these metrics are scattered in a larger number of studies, where many do not explain what these metrics should measure. Therefore, this paper presents a research about SM metrics’ adoption in Brazilian software companies. We performed semi-structured interviews in a face-to-face fashion with 10 software companies resulting in 23 SM metrics listed, and 14 tools for supporting SM metrics collection. Our results showed evidence that most of the SM metrics proposed by researchers are not used by practitioners.